Passive acoustic monitoring data recorded by recorder SV1003 at mooring AWI250-2 in the Weddell Sea, Southern Ocean, in 2017/2018 - Karolin Thomisch; Stefanie Spiesecke; Diego Filun; Ramona Mattmüller; Marlene Meister; Sarah Zwicker; Olaf Boebel (PANGAEA, 2025)
Passive acoustic monitoring (PAM) data were collected by recorder SV1003 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 68.464° S, 44.1452° W, mooring AWI250-2, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from January 2017 to January 2019, passive acoustic data were collected from January 2017 to November 2018 (recording period) by SV1003 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 1036 m depth and scheduled to record continuously at a sample rate of 6,857Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 2+ (see Data Processing Report), deviating from Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).